2010
DOI: 10.1007/s10661-010-1563-8
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater stress and vulnerability in rural coastal aquifers under competing demands: a case study from Sri Lanka

Abstract: Rural coastal aquifers are undergoing rapid changes due to increasing population, high water demand with expanding agricultural and domestic uses, and seawater intrusion due to unmanaged water pumping. The combined impact of these activities is the deterioration of groundwater quality, public health concerns, and unsustainable water demands. The Kalpitiya peninsula located northwest of Sri Lanka is one area undergoing such changes. This land area is limited and surrounded almost completely by sea and lagoon. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The human and sanitation nitrogen loading of 14.3 g per capita per day was estimated assuming that the ammonia concentration is negligible based on Jayasekara et al (2011). Agricultural nitrogen loadings were estimated using the fertilizer and irrigation nitrogen loadings observed through on-site measurements and interviews.…”
Section: Modified Drastic Methodsmentioning
confidence: 99%
“…The human and sanitation nitrogen loading of 14.3 g per capita per day was estimated assuming that the ammonia concentration is negligible based on Jayasekara et al (2011). Agricultural nitrogen loadings were estimated using the fertilizer and irrigation nitrogen loadings observed through on-site measurements and interviews.…”
Section: Modified Drastic Methodsmentioning
confidence: 99%
“…Other studies have found high levels of nitrate-N in groundwater (Mikunthan and de Silva 2009;Jeyaruba and Thushyanthy 2009), which have been directly related to agricultural activities ( (Jayasingha et al 2011;Liyanage et al 2000); Kuruppuarachchi and Fernando 1999;(Nagarajah et al 1988)). Overextraction of groundwater resources has also contributed to saltwater intrusion and higher nitrate loads in the groundwater (Jayasekera et al 2011;Jayasekera 2007). The existence of too many wells also leads to salinization of the aquifer (Nandakumar 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Adding to their complex emergence environment, springs often support a wide array of microhabitats not observed in wetlands. The "sphere" into which the aquifer discharges was initially described by Meinzer (1923), and then simplified by Hynes (1970) into three classes: rheocrene (channel emergence), limnocrene (pool emergence), and helocrene (wet meadow emergence). Springer et al (2008) and Springer and Stevens (2009) reviewed literature and expanded this historical scheme to include 12 spheres of discharge of terrestrial springs, including: (1) springs that emerge in caves, (2) exposure springs, (3) artesian fountains, (4) geysers, (5) gushets, (6) contact hanging gardens, (7) helocrene wet meadows, (8) hill slope springs, (9) hypocrene buried springs, (10) limnocrene surficial lentic pools, (11) mineralized mounds, and (12) rheocrene lotic channel floors.…”
Section: Classification Of Springs Ecosystems As Gdesmentioning
confidence: 99%
“…Reduced groundwater pressure and flux cause reduced groundwater discharge and subsequently reduced surface water availability to wetlands and GDEs that depend on base flow and springs (Zektser et al 2005). In estuary or coastal areas reduced groundwater flux leads to seawater intrusion and contamination of coastal freshwater aquifers (Jayasekera et al 2011;Lambrakis 1998), thereby reducing groundwater quality. For cave and aquifer ecosystems, appropriate groundwater flux is important to maintain a supply of organic matter and oxygen (Hancock et al 2005) to stygofauna contained within these systems.…”
Section: Plantation Forestrymentioning
confidence: 99%